TERAPI MUSIK SEBAGAI LOWERING DEPRESI POSTPARTUM PADA WANITA PASCA-MELAHIRKAN - Rabi`atul Apriyanti (Khazanah: Jurnal Mahasiswa, 2016)
According to some researches, 85% major depression followed by anxiety. Many research about anxiety especially experimental research shows that mu sic therapy has a significant effect to reduce anxiety and increase positive emotions. Music therapy has two roles or goals that are reinforcement and punishment. In this paper, the writer focus on music therapy as reinforcement or drivers of behavior change toward more positive. Expected that these changes can be settled, attached, and continuous on related individuals. Based on those explanation assumed that music therapy can be used with its role as a reinforcement to be lowering the intensity of postpartum depression in some women postpartum. This paper written with library study methods and techniques of content analysis.Keywords: postpartum depression, woman, music therapy, lowering, reinforcement